Optimasi Kecepatan Pengadukan dan Waktu Kontak Zat Warna Metanil Yellow terhadap C-SinamalKaliks [4] Resorsinarena (CSKR) - Aminullah Mimi Darwati; Sri Benti Etika; Fitri Amelia (Jurnal Periodic Jurusan Kimia UNP, 2021)
Abstract — Uncontrolled handling of industrial waste disposal systems causes pollution to the environment by hazardous materials such as dyes. Activities that cause the excessive discharge of dyes come from the textile, paper, pigment and paint industries. This industrial activity releases dyestuffs that enter through the food chain so that it has a bad impact on human health. One of the alternative methods used in tackling dye waste pollution is adsorption. Organic compounds that have great potential to be used as adsorbents to absorb dyes are C-Sinamalkaliks [4] Resorsinarene (CSKR). This study uses CSKR to absorb dye which aims to determine the potential of C-SinamalKaliks [4] Resorsinarene (CSKR) which is an adsorbent for the absorption of the dye methanyl yellow. This research was conducted using a batch method with various treatments of stirring speed and contact time. The results showed that the optimum absorption of metanyl yellow against CSKR was at the contact time of 150 minutes and the stirring speed of 100 rpm with an absorption capacity of 2.13 mg/g.